Los Fondos de Inversión en el Perú y el Impuesto a la Renta - Polo Chiroque, Roberto E. (Pontificia Universidad Católica del Perú, 2016)
The investment funds provide an alternative investment mechanism to traditional ones such as banks deposits or the trading of securities, which allows us to obtain profitability as a result of the development of multipleactivities, including commercial ones.Its tax treatment, and particularly in the field of Income Tax, contains severalprovisions that are important to analyze and know in order to understand the tax consequences that generate both for their promoters, for those who administer them and for investors.Being transparent vehicles for tax purposes, the development of its activities at the national level and with the participation of foreign capitals, takes many details that we will explain through this article.

Los Fondos de Inversión constituyen un mecanismo de inversión alternativo a los tradicionales como los depósitos bancarios o la negociación de valores, que permite obtener rentabilidad producto del desarrollo de múltiples actividades, incluyendo las de tipo comercial.Su tratamiento impositivo, y en particular en materia del Impuesto a la Renta,contiene diversas disposiciones que son importantes de analizar y conocer a efecto de entender las consecuencias fiscales que generan tanto para sus promotores, como para quienes los administran y para los inversionistas. Siendo vehículos transparentes para propósitos fiscales, el desarrollo de sus actividades a nivel nacional y con la participación de capitales extranjeros reviste varios matices que mediante este trabajo expondremos.
The investment funds in Peru and the Income Tax
Keywords: Fund; Investment; Taxes; Safi; Attribution; Retention; Firbi; Fondo; Inversión; Impuestos; Safi; Atribución; Retención; Firbi; https://purl.org/pe-repo/ocde/ford#5.05.00